Production Process Of HR Sukoco’s Song "Seleh" on a Digital Music Platform - Putri, Lutfi; Hidajad, Arif (Solah, 2026)
Heru Sukoco, a newcomer musician from Ponorogo who creates original songs, one of which is entitled Seleh. He successfully produced the song Seleh independently through three stages, namely pre-production, production, and post-production. The purpose of this study is to find out how Heru Sukoco’s process of producing music up to the stage of marketing songs on digital music platforms. This study uses a descriptive qualitative method with data collection techniques through interviews with informants, observations, and literature studies. The data obtained were then analyzed by reduction and triangulation, and presented in narrative form. To ensure the credibility of the data, data verification and validation were carried out. This study resulted in a description of the production process to the marketing process of the song Seleh carried out by Heru Sukoco through stages starting from pre-production, production, to post-production which includes the process of arrangement, tracking, recording, mixing, and mastering, until entering the digital music platform.